ATP-Dependent Clp Protease Subunit C1, HvClpC1, Is a Strong Candidate Gene for Barley Variegation Mutant luteostrians as Revealed by Genetic Mapping and Genomic Re-sequencing - Li, Mingjiu; Guo, Ganggang; Pidon, Hélène; Melzer, Michael; Prina, Alberto R.; Börner, Thomas; Stein, Nils (Frontiers in Plant Science, 2021)
Implementation of next-generation sequencing in forward genetic screens greatly accelerated gene discovery in species with larger genomes, including many crop plants. In barley, extensive mutant collections are available, however, the causative mutations for many of the genes remains largely unknown. Here we demonstrate how a combination of low-resolution genetic mapping, whole-genome resequencing and comparative functional analyses provides a promising path towards candidate identification of genes involved in plastid biology and / or photosynthesis, even if genes are located in recombination poor regions of the genome. As a proof of concept, we simulated the prediction of a candidate gene for the recently cloned variegation mutant albostrians (HvAST / HvCMF7) and adopted the approach for suggesting HvClpC1 as candidate gene for the yellow-green variegation mutant luteostrians.